Figurative Language in Billie Eilish’s Guitar Songs: ‘TV’ and ‘The 30th’ - Tsalis Lutfi Sa’diyah; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes the use of figurative language in two songs from the EP. Guitar Songs Billie Eilish, namely ‘TV’ and ‘The 30th’. Language is an essential communication tool, but understanding non-literal meanings is often a challenge, especially in works of art such as songs. This study aims to identify and classify the types of figurative language used, analyze its contextual meaning in relation to emotional and thematic content, and explain its role as a medium for psychological reflection and social commentary in contemporary songwriting. Using a qualitative descriptive research design and textual analysis approach, this study applies Geoffrey Leech's (1969) taxonomy to categorize figurative expressions. The findings show diverse types of figurative language such as metaphor, irony, hyperbole, personification, allusion, idiom, repetition, and imagery, which collectively convey complex emotional states and critique contemporary social issues. This research contributes to the understanding of song lyrics as meaningful texts that reflect the reality of the postmodern generation.